To Like or Not to Like? An Experimental Study on Relational Closeness, Social Grooming, Reciprocity, and Emotions in Social Media Liking. Issue 2 (16th January 2023) - Stsiampkouskaya, Kseniya; Joinson, Adam; Piwek, Lukasz
Abstract: We conducted a randomized-controlled experiment with 201 participants to investigate the effects of relationship closeness, emotions, and the receipt of Likes on reciprocal Liking behaviors. We found that individuals engaged in interchange-oriented social grooming by giving Likes to close friends regardless of whether they had received Likes from them before. However, when relationship closeness was low, participants mirrored their acquaintances' behavior by reciprocating Likes for Likes. Additionally, high-arousal positive emotions mediated the effects of receiving Likes on the intention to Like other users' content, but this result only held true when relational closeness was not accounted for in the model. Our study explains why people give Likes on social media and what factors shape their Liking intentions. The results of our study contribute to the existing knowledge of the social norm of reciprocity, social grooming, emotion regulation, relational closeness, and social media Liking. Lay Summary: The study investigates whether social media users reciprocate Likes from close friends and acquaintances and what role emotions play in this process. We conducted an online experiment and allocated participants to one of the following groups: receiving a Like from a close friend, not receiving a Like from a close friend, receiving a Like from an acquaintance, and not receiving a Like from an acquaintance. We found that people tend to return Likes for Likes and that individuals feel excited and enthusiastic after receiving a Like from another user. We also discovered that this emotional response prompts them to Like that user's content in the future. However, the results suggest that relational closeness plays a more important role than emotions in Likes reciprocation. Specifically, people are motivated by relationship maintenance rather than reciprocity when it comes to close friendship. When a person sees a post shared by their close friend, they tend to Like it, even if this close friend did not Like that person's previous post. When it comes to acquaintances, people are driven by the social norm of reciprocity and tend to give Likes only to those who Liked their content before. Hence, the study clarified the role of emotions and relational closeness in the reciprocation of Likes on social media.